2002
DOI: 10.1002/mds.10198
|View full text |Cite
|
Sign up to set email alerts
|

Depression leading to attempted suicide after bilateral subthalamic nucleus stimulation for Parkinson's disease

Abstract: Subthalamic nucleus stimulation is emerging as an effective surgical therapy for Parkinson's disease. It is considered to be a safe procedure with little morbidity, the most common complications being intracranial haemorrhage and hardware failure. We report on three cases of depression, one of whom attempted suicide after bilateral subthalamic nucleus stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
2
7

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(104 citation statements)
references
References 8 publications
3
90
2
7
Order By: Relevance
“…However, transient euphoria and manic psychosis or anhedonia and depression were also reported to compromise the motor benefit of STN stimulation in the first weeks after device implantation Doshi et al, 2002;Krack et al, 2001Krack et al, , 2002Volkmann et al, 2001). In our small PD study sample, severe neuropsychiatric side effects were observed in three out of eight patients within the first 6 weeks after surgery.…”
Section: Figmentioning
confidence: 64%
“…However, transient euphoria and manic psychosis or anhedonia and depression were also reported to compromise the motor benefit of STN stimulation in the first weeks after device implantation Doshi et al, 2002;Krack et al, 2001Krack et al, , 2002Volkmann et al, 2001). In our small PD study sample, severe neuropsychiatric side effects were observed in three out of eight patients within the first 6 weeks after surgery.…”
Section: Figmentioning
confidence: 64%
“…There is evidence that DBS may also worsen depression and mania, increase apathy, affect emotional lability, and increase the risk of suicide (Berney et al, 2002;Doshi et al, 2002;Okun et al, 2003Okun et al, , 2009Funkiewiez et al, 2004;Smeding et al, 2005Smeding et al, , 2006Drapier et al, 2008;Voon et al, 2008). Mood problems are more common in patients treated with STN-DBS than those treated with GPi-DBS Follett et al, 2010;Moro et al, 2010;Bronstein et al, 2011).…”
Section: Non-motor Side Effects Of Stn and Gpi-dbsmentioning
confidence: 99%
“…There were 4 Class III studies [36][37][38][39] and 10 Class IV studies. [40][41][42][43][44][45][46][47][48][49] All studies examined bilateral DBS of the STN. Only the Class III studies are discussed in detail.…”
Section: Surgical Therapy Question 4: For Patients With Pd Does Dbsmentioning
confidence: 99%
“…[36][37][38][39][40][41]43,44,[46][47][48][49] Only the Class II studies are discussed in detail. Although these studies were rated Class IV relative to Question 4 regarding efficacy, they earned grades of Class II relative to prognosis for Question 5.…”
Section: Question 5: Which Factors Predict Improvement After Dbs?mentioning
confidence: 99%